Teaching of Chinese Degree Adverb Synonymous with the Meaning of “very” for Occidental Students at the Beginning Level: A Case Study of Chinese Beginner in Yunnan Normal University (Sinología hispánica. China Studies Review, 2017)
This study focuses on one of the importantand difficult language points in teachingChinese as the second language, synonymousdegree adverbs in modern Chinese language,aiming at the beginning level of occidentalstudents who excessively rely on their mothertongue. The research has been done byobserving a group of typical adverbs with themeaning of “very” in Chinese language, such as"feichang, shifen, hen, ting, ji" in combinationwith ontology and error analysis and classroomtesting. The paper explores the reasons andtypes of errors, and designs the teaching planaccording to the testing results. Comparing thetesting results, it is suggested that comparewith error analysis, language testing combinedwith inductive reasoning is more effective inteaching synonymous degree adverbs in modernChinese language.